PEMANFAATAN SMS GATEWAY DALAM APLIKASI PENGOLAHAN DATA INVENTARIS PERALATAN PRAKTEK PADA SMK PRASASTI KARANG BERAHI KOTA JAMBI: APPLICATIONS, BOOTSTRAP, FRAMEWORK,Â INFORMATION, INVENTORY, MYSQL, PHP, SMS GATEWAY - Limia Budiarti, Rike; Sany, Ezrifal; Wahid, Nur (LP2M STMIK Nurdin Hamzah Jambi, 2017)
Technological advances force all lines to continue to innovate and adapt to technology. This led to a variety of problems that make technological advocates continue to be given space to innovate. From the background found in SMK Prasasti Karang Berahi Kota Jambi in the application of inventory data processing is still relatively simple, inventory inventory data inventory is done manually by writing / note on the agenda book and some data input done by using microsoft office application. To help this activity needs to be created or designed a program or application that can be used simultaneously and can run on all existing computer browsing software installed. Data Processing Applications Inventory Tools Practices are built using web-based technology with PHP scripting languages, MySQL databases, and Freamwork. With the implementation of Web-based Inventory Data Processing Applications in SMK Prasasti Karang Berahi this affects the school, etc. and helps administrative data collection staff in delivering inventory of online and online practice equipment because the data is presented quickly. SMS Gateway as one of the solutions offered to provide easy access to information.